Sustainability Analysis of the Stunting Reduction Acceleration Program in Kubu Raya Regency - Resky Nanda Pranaka; Evi Gusmayanti; Indah Budiastutik; Malik Saepudin; Havid Aqoma (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Presidential Regulation Number 72 of 2021 on the Acceleration of Stunting Reduction sets a national target of reducing stunting prevalence to 14% by 2024 through integrated programs across government levels, from ministries to villages. In line with this policy, Kubu Raya Regency has shown a decline in stunting rates from 7.9% to 6.8% based on e-PPGBM data, indicating improved implementation of stunting reduction programs. This study aims to analyze the sustainability status of the stunting reduction program in Kubu Raya Regency using the Rapfish (Rapid Appraisal for Fisheries) multidimensional scaling approach. Data were collected from ten Regional Apparatus Organizations (OPDs) through surveys and interviews. The analysis involved six stages: identifying dimension characteristics, scoring on an ordinal scale, determining sustainability status, conducting sustainability checks, performing a sensitivity analysis, and applying a Monte Carlo simulation to account for uncertainty. The results show that the social and economic dimensions are categorized as